EFFECT OF BENZYLADENINE AND CHEMICAL FERTILIZATION ON GROWTH, FLOWERING AND CHEMICAL COMPOSITION OF JASMINUM SAMBAC PLANT - E. Abou El-Ghait; A. Youssef; Y. Mohamed; Tarek Noor El-Deen; Heba Mohamed (Scientific Journal of Flowers and Ornamental Plants, 2020)
A pot experimental study was carried out at the Floriculture Nursery of the Horticulture Department, Faculty of Agriculture at Moshtohor, Benha University, Egypt during 2017 and 2018 seasons to study the effect of 16 treatments represented the combination between foliar spraying with four benzyladenine (BA) concentrations (0.0, 20, 40 and 60 ppm) and four chemical fertilization rates (0.0, 2, 4 and 6 g NPK/pot) on the growth, flowering and chemical composition of Arabian jasmine plant (Jasminum sambac Ait). The obtained results cleared that the tallest plants, the highest number of branches and leaves, the heaviest leaves fresh weight/plant, the highest number of flowers/plant, the heaviest flowers fresh weight/plant, the highest number and length of roots/plant, the heaviest fresh weight of roots/plant as well as the richest leaf total carbohydrates, nitrogen, phosphorus and potassium percentages were obtained by those treated with BA at 60 ppm + chemical fertilization at 6 g/pot in the two seasons.  Conclusively, sprayingjasmine plants with BA at 60 ppm and supplying the plants with NPK mineral fertilizer at 6 g/pot, induced prospective effects on vegetative growth and flowering parameters with higher quality of this plant